2016
DOI: 10.1245/s10434-016-5286-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Clinical Response with Talimogene Laherparepvec (T-VEC) in Patients with Melanoma Treated in the OPTiM Phase III Clinical Trial

Abstract: PurposeTalimogene laherparepvec (T-VEC) is an oncolytic immunotherapy designed to induce tumor regression of injected lesions through direct lytic effects, and of uninjected lesions through induction of systemic antitumor immunity. In this study, we describe the patterns and time course of response to T-VEC from the phase III OPTiM trial of 436 patients with unresected stages IIIB–IV melanoma.MethodsLesion-level response analyses were performed based on the type of lesion (injected or uninjected cutaneous, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(214 citation statements)
references
References 18 publications
8
194
2
1
Order By: Relevance
“…In the pivotal single agent study of talimogene laherparepvec, a decrease in tumor size was observed in 15% of evaluable, noninjected, measurable visceral lesions (Andtbacka et al, 2015;Andtbacka et al, 2016). We also observed Figure 6) it is possible that the late timing of the biopsies (with week 6 occurring 2 weeks after the previous talimogene laherparepvec injection) was not optimal to address this question.…”
Section: Changes In the Functional Phenotype Of Circulating T Cells Wmentioning
confidence: 77%
“…In the pivotal single agent study of talimogene laherparepvec, a decrease in tumor size was observed in 15% of evaluable, noninjected, measurable visceral lesions (Andtbacka et al, 2015;Andtbacka et al, 2016). We also observed Figure 6) it is possible that the late timing of the biopsies (with week 6 occurring 2 weeks after the previous talimogene laherparepvec injection) was not optimal to address this question.…”
Section: Changes In the Functional Phenotype Of Circulating T Cells Wmentioning
confidence: 77%
“…In contrast, patients in the Amgen trial of talimogene laherparepvec in adults had slowly growing, albeit advanced stage, melanoma. In the melanoma trial, the average time to disease response was 4 months and patients were injected with 10 8 infectious units of virus every 2 weeks for a minimum of 24 weeks, despite disease progression during that time (1,22). Rather than from a direct lytic effect, the implication is that the majority of response resulted from antitumor immunity, which may take weeks to months to become robust.…”
Section: Discussionmentioning
confidence: 99%
“…Oncolytic herpes viruses (oHSVs) are members of an emerging class of cancer therapeutics that can selectively infect, replicate in, and lyse tumor cells without causing significant damage to the surrounding normal stroma 7 . Although these direct lytic effects are important in themselves, they can also promote an adaptive antitumor immune response that can help eradicate local tumors and distant metastases alike 8, 9. The most pertinent example of this immunologic activity is currently found in Imlygic (Talimogene Laherparepvec), an oHSV that encodes the gene for granulocyte-macrophage colony-stimulating factor and the first oncolytic virus to be approved by the US Food and Drug Administration (FDA) as a cancer therapeutic.…”
Section: Introductionmentioning
confidence: 99%